Perspektif Islam terhadap “Kaum Majusi” Modern - Ayuni, Farihah; Rahayu, Gina Selvia; Nadhirah, Nesty Ermin; Gustavisiana, Tegar Selaras; Fajrussalam, Hisny (Lembaga Yasin AlSys, 2023)
In this modern era, we often encounter celebrations by blowing out candles as part of the event. This continues to develop and grow into a culture in society. As for Islam, it strictly prohibits a celebration in which there is uproar and blowing out candles as the culmination of the event because it seems to have cultivated the habits of the former Magi. However, some other Muslims actually think that blowing out candles at a celebration is a sign of gratitude. This research is aimed at analyzing how many people cultivate candle blowing in celebrations and how Muslims view blowing candles at a celebration because this problem reaps pros and cons from Muslims themselves. The methods to be used in this research are qualitative and quantitative methods, considering the level of direct data requirement for this research.